2005
DOI: 10.1679/aohc.68.227
|View full text |Cite
|
Sign up to set email alerts
|

Krox-20 gene expression: Influencing hindbrain-craniofacial developmental interactions

Abstract: Krox-20 is a C(2)H(2)-type zinc-finger transcription factor that plays an essential role in hindbrain development. The Krox-20 null mutation results in hindbrain anomalies that result in neonatal death due to respiratory and feeding deficits. Here we review our studies of how the Krox- 20 null mutation impacts the development of motor and sensory systems critical for the production of consummatory behaviors (suckling/chewing). First, we demonstrated that Krox-20 null mutants suffer a selective loss of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Like EGR1 [5], EGR2 transcription is suppressed in part by PLZF induction as hESCs decidualize. A pleiotropic transcription factor EGR2 is required for a broad range of biological responses from hindbrain ontogenesis to T-cell development and function [28,29]. Interestingly, recent studies have revealed that EGR2 directly binds to the promoter of the PLZF gene to promote invariant (i)NKT cell development and function [30].…”
Section: Discussionmentioning
confidence: 99%
“…Like EGR1 [5], EGR2 transcription is suppressed in part by PLZF induction as hESCs decidualize. A pleiotropic transcription factor EGR2 is required for a broad range of biological responses from hindbrain ontogenesis to T-cell development and function [28,29]. Interestingly, recent studies have revealed that EGR2 directly binds to the promoter of the PLZF gene to promote invariant (i)NKT cell development and function [30].…”
Section: Discussionmentioning
confidence: 99%
“…4). Therefore, these results suggested Egr2, the known critical transcription factor for PNS myelination and also for hindbrain development 17,18 , as a possible master mediator for the effect of SI and resocialization.…”
Section: Immediate Resocialization Rescued Mice's Cooperation Defect mentioning
confidence: 85%
“…We further introduce Egr2 as a molecular player, acting within Drd1 + neurons of the VLS to promote the development of drug seeking. Previous studies have showed that Egr2 is crucial for normal hindbrain development, peripheral myelination, humoral immune response, and implicated in diseases such as congenital hypomyelinating neuropathy, Charcotā€“Marie-Tooth disease, Dejerineā€“Sottas syndrome, as well as Schizophrenia (Boerkoel et al, 2001; De and Turman, Jr., 2005; Li et al, 2019; Morita et al, 2016; Okamura et al, 2015; Svaren and Meijer, 2008; Topilko et al, 1994; Warner, 1999; Warner et al, 1998; Wilkinson, 1995; Yamada et al, 2007). In the central nervous system, Egr2 has been shown to be induced by seizure activity, kainic acid injection, following LTP-inducing stimuli in hippocampal neurons, as well as following administration of several groups of drugs such as methamphetamine, cocaine, heroin, and alcohol (Gao et al, 2017a; Gass et al, 1994; Imperio et al, 2018; LĆ³pez-LĆ³pez et al, 2017; Mataga et al, 2001; Rakhade et al, 2007; Saint-Preux et al, 2013; Worley et al, 1993).…”
Section: Discussionmentioning
confidence: 99%